1999
DOI: 10.1002/(sici)1098-108x(199904)25:3<349::aid-eat15>3.3.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

The reliability of the eating disorder examination—Self‐report questionnaire version (EDE‐Q)

Abstract: Objective: This research investigated the internal consistency and test-retest reliability of the Eating Disorder Examination-Self-Report Questionnaire Version (EDE-Q), a 41-item measure adapted from the Eating Disorder Examination (EDE). The EDE is a structured clinical interview assessing the key behavioral features and associated psychopathology of eating disorders. Results: Results indicated excellent internal consistency and 2-week test-retest reliability for the four subscales of the EDE-Q: Restraint, We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
123
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(135 citation statements)
references
References 1 publication
(1 reference statement)
12
123
0
Order By: Relevance
“…The global score represents the mean of the four subscale scores. Different studies showed that EDE-Q has an adequate test-retest reliability [21], good convergence with the EDE interview [22,23], and both discriminant and concurrent validity [24].…”
Section: Evaluation Instrumentssupporting
confidence: 91%
“…The global score represents the mean of the four subscale scores. Different studies showed that EDE-Q has an adequate test-retest reliability [21], good convergence with the EDE interview [22,23], and both discriminant and concurrent validity [24].…”
Section: Evaluation Instrumentssupporting
confidence: 91%
“…The EDE-Q has high internal consistency (Luce & Crowther, 1999), with moderate to high concurrent and criterion validity (Fairburn & Beglin, 1994). The Cronbach's alpha in this study was 0.93.…”
Section: Methodsmentioning
confidence: 57%
“…Binford et al 2005). Test-retest reliability coefficients for subscales range from .81 to .94 and Cronbach alphas range from .78 to .93 (Luce and Crowther 1999). It also shows high correlations with all subscales of the EDE (r = .71 to .90), although the EDE tends to capture more bulimic pathology (Binford et al 2005).…”
Section: Methodsmentioning
confidence: 99%